2014
DOI: 10.1188/14.cjon.e45-e49
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Music on Pain and Anxiety During Screening Mammography

Abstract: One in four women who are diagnosed with breast cancer die annually, and the single most important way to prevent this is early detection; therefore, women older than 40 years should have an annual screening mammography. Many barriers have been reported that prevent compliance with this recommendation, including lack of insurance, fear, anxiety, pain, worry, and mistrust of the medical community. Nurses are in a position to use creative interventions, such as music therapy, to help minimize barriers. Although … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 15 publications
0
15
0
2
Order By: Relevance
“…Boehm et al found a clinically and statistically significant mean difference ( P < .01) in the anxiety scores of patients who received music therapy compared with the control group, thus further supporting our recommendation of passive music therapy for reducing anxiety. Passive music therapy has also been shown to reduce anxiety among patients undergoing mammographic screening, indicating that the recommendation may apply broadly to adult women in a clinical cancer setting …”
Section: Literature Review On the Use Of Complementary And Integrativmentioning
confidence: 99%
See 1 more Smart Citation
“…Boehm et al found a clinically and statistically significant mean difference ( P < .01) in the anxiety scores of patients who received music therapy compared with the control group, thus further supporting our recommendation of passive music therapy for reducing anxiety. Passive music therapy has also been shown to reduce anxiety among patients undergoing mammographic screening, indicating that the recommendation may apply broadly to adult women in a clinical cancer setting …”
Section: Literature Review On the Use Of Complementary And Integrativmentioning
confidence: 99%
“…Passive music therapy has also been shown to reduce anxiety among patients undergoing mammographic screening, indicating that the recommendation may apply broadly to adult women in a clinical cancer setting. 323 Risk/benefit assessment of music therapy. Passive music therapy is noninvasive, does not interfere with a patient's privacy, and has no reported deleterious effects.…”
Section: Music Therapy (B Grade)mentioning
confidence: 99%
“…Although this study did not show that music therapy during screening mammograms decreased the amount of pain experienced by the subjects, it did suggest that music therapy has the potential to decrease the amount of anxiety. The authors concluded that assisting patients in decreasing anxiety also reduces barriers for screening mammography, which might be helpful in increasing the rates of such uncomfortable screening tools [7]. Interestingly, similar findings have been reported for patients receiving routine colonoscopies.…”
mentioning
confidence: 65%
“…None of these studies were conducted exclusively with the intention of assessing distress at the time of screening. Previous studies assessed distress associated with false-positive results, [15][16][17][18]23,29 interventions to decrease preprocedural distress, test result fears, worries about cancer diagnosis, 19,21,24,25,27,30 or psychosocial constructs (eg, anxiety/worry. social support, perceived risk) associated with cancer screening.…”
Section: Resultsmentioning
confidence: 99%
“…[15][16][17][18][19][20][21][22][23][24] The validated measures consisted of the Spielberger State-Trait Anxiety Inventory (STAI), 37 The 6-question short form of the Spielberger State-Trait Inventory (STAI-6), 38 Hopkins Symptom Checklist subscales for Anxiety (HSC-A), 39 the Impact of Events Scale (IES), 49 the Penn State Worry Questionnaire (PSWQ), 40 the Beck Anxiety Inventory (BAI), 41 the Health Utility-European Quality-of-Life (EuroQol) instrument (EQ-5D), 42 the Zung Anxiety Self-Assessment Scale, 43 and the Symptom Checklist 90-Revised (SCL-90) 44 (see Table 1 and Supporting Table 4 [in the online information] for scoring details). [15][16][17][18][19][20][21][22][23][24] The validated measures consisted of the Spielberger State-Trait Anxiety Inventory (STAI), 37 The 6-question short form of the Spielberger State-Trait Inventory (STAI-6), 38 Hopkins Symptom Checklist subscales for Anxiety (HSC-A), 39 the Impact of Events Scale (IES), 49 the Penn State Worry Questionnaire (PSWQ), 40 the Beck Anxiety Inventory (BAI), 41 the Health Utility-European Quality-of-Life (EuroQol) instrument (EQ-5D), 42 the Zung Anxiety Self-Assessment Scale, 43 and the Symptom Checklist 90-Revised (SCL-90) 44 (see Table 1 and Supporting Table 4 [in the online information] for scoring details).…”
Section: Measures Of Distressmentioning
confidence: 99%